Effect of interleukin 17 on proteoglycan degradation in murine knee joints. Issue 7 (1st July 2000) - Dudler, Jean; Renggli-Zulliger, Nicole; Busso, Nathalie; Lotz, Martin; So, Alexander
Abstract : OBJECTIVE: To evaluate the effect of murine interleukin 17 (IL17) on cartilage catabolism and joint inflammation by direct intra-articular injection of the cytokine into murine knee joints. METHODS: Knees of normal C57 Bl mice were injected once or repeatedly with recombinant IL17 or IL1β. Inflammation was estimated by technetium-99m pertechnetate ( 99 Tc) uptake and histological scoring of tissue sections. Proteoglycan depletion was evaluated by histological scoring of safranin O stained sections. Effects on proteoglycan synthesis were studied by 35 SO4 incorporation. RESULTS: A single intra-articular injection of IL17 (10 ng/knee) produced effects very similar to those of IL1β (10 ng/knee). No inflammation was detected at six or 24 hours by 99 Tc uptake. However, safranin O staining showed depletion of proteoglycan at 48 hours. Repeated injections of IL17 induced joint inflammation and cartilage proteoglycan depletion as shown by histological scoring. Unlike IL1β, proteoglycan depletion induced by IL17 seemed to be the result of increased degradation only, as no suppression of 35 SO4 incorporation was seen. CONCLUSION: These findings confirm, in vivo, the catabolic effects of IL17 on cartilage. IL17 is thus the first T cell cytokine showing a direct catabolic effect on cartilage in addition to stimulatory effects on macrophages and synoviocytes, making it a potentially important cytokine in the pathogenesis of arthritis.